2019
DOI: 10.3889/oamjms.2019.299
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Albendazole and Mebendazole With or Without Levamisole for Ascariasis and Trichuriasis

Abstract: BACKGROUND: Helminthiasis in school-aged children potentially causing physical growth and intellectual development retardation. Trichuriasis was the most common type of helminthiasis in children. AIM: To investigated the efficacy and side effects of albendazole, albendazole combined with levamisole and mebendazole combined with levamisole for trichuriasis and ascariasis. METHODS: This study was conducted as a double-blind, randomised clinical trial by comparing the efficacy and side effects of albe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, egg reduction (ER) by albendazole was 40%. 12 Mebendazole showed better results with 19% CR, increased to 55% if combined with ivermectin, and 83.3% if combined with levamisole; the ER was 67%. 13 The efficacy of albendazole and mebendazole was better if combined with levamisole or ivermectin, 12,13 but those drugs are not available in Papua, so we used monotherapy in our cases.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, egg reduction (ER) by albendazole was 40%. 12 Mebendazole showed better results with 19% CR, increased to 55% if combined with ivermectin, and 83.3% if combined with levamisole; the ER was 67%. 13 The efficacy of albendazole and mebendazole was better if combined with levamisole or ivermectin, 12,13 but those drugs are not available in Papua, so we used monotherapy in our cases.…”
Section: Discussionmentioning
confidence: 90%
“…The recommended target populations have expanded from only school-aged children to include Anthelmintic treatment efficacy data against Trichuriasis are limited and varied. A previous study showed that the efficacy of albendazole vs. mebendazole in Trichuriasis was not consistent; one study revealed that albendazole alone had an 88.3% cure rate (CR), 12 but another study reported only a 10% CR. 13 The CR after combination ivermectin treatment was 38%, and after combination with levamisole was 95.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies including a few conducted in Malaysia revealed low curative effect (< 50.0%) of the albendazole against T. trichiura, which reportedly ranged between 4.9-50.0% (Ramalingam et al, 1983;Chien et al, 1989;Sinniah et al, 1990;Albonico et al, 1994;Norhayati et al, 1997;Bennett & Guyatt, 2000;Keiser & Utzinger, 2008). On the other hand, a few studies claimed > 50% cure rate, for instance: 68.9% cure rate in the Philippine (Ovedoff, 1984), 83.9% in Kenya (Bwibo & Pamba, 1984), 52.7% in Haiti (Beach et al, 1999), 76.0% in France and West Africa (Pene et al, 1982) and 81.7% in Indonesia (Anto & Nugraha, 2019). The reason behind these huge disparities is still unknown and many factors have been suggested which includes the possibility of anthelminthic resistance or reduced efficacy of the drugs by underdosing (Vercruysse et al, 2011;Shalaby, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of anthelmintic treatment, sometimes the clinical treatment method of combined medication is adopted. Anto and Nugraha conducted a double-blind randomized clinical trial to compare the efficacy and side effects of albendazole, albendazole combined with levamisole and mebendazole combined with levamisole in the treatment of trichomoniasis [ 45 ]. The results showed that the cure rate of albendazole combined with levamisole for mild caterpillar disease and mixed infection was better, and the side effects of all treatment groups were similar.…”
Section: Bench Study: Exploration Of the Pharmacological Activity Of ...mentioning
confidence: 99%